2005
DOI: 10.1051/kmae:2005027
|View full text |Cite
|
Sign up to set email alerts
|

Of Sodium Nitrite for Spiny-Cheek Crayfish (Orconectes Limosus Raf.) the Effect of Chloride Content in Water on the Toxicity

Abstract: Toxicity of sodium nitrite for the spiny-cheek crayfish (Orconectes limosus) was assessed in relation to the concentration of chlorides diluted in water. Results of the tests confirmed a favourable effect of chloride content in water on the tolerance of spiny-cheek crayfish to nitrites. The 96hLC 50 value of 4.8 mg l -1 , 17.7 mg l -1 , 34.7 mg l -1 , 50.5 mg l -1 , 74.4 mg l -1 , and 96.6 mg l -1 N-NO 2 -found out in individual tests corresponded, respectively to a chloride content of 11, 40, 100, 200, 300 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…For example, a previous study found that the slc26a6 gene of the nakedcarp (Gymnocypris przewalskii) was expressed in various tissues, such as gills, liver, kidneys and intestines, and that the upregulation of SLC26A6 increased HCO3 − secretion and the Cl − absorption in the cells (Ping et al, 2015). Notably, several studies have shown that elevated chloride concentrations in the aquatic environment reduce the toxic effects of nitrite on aquatic animals, because both nitrite ions and chloride ions compete for the same site of active transport (Alcaraz and Espina, 1994;Jiann-Chu and Lee, 1997;Sha-Yen and Chen, 1998;Yildiz and Benli, 2004;Kozák et al, 2005;Camargo and Alonso, 2006;Alonso and Camargo, 2008;Zhang et al, 2015). Therefore, we hypothesized that the upregulation of SLC26A6 in nitrite-tolerant shrimp increases the absorption of chloride ions, forcing chloride ions and nitrite ions compete for the same site of active transport on the plasma membrane and various organelle membranes, resulting in enhanced nitrite tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous study found that the slc26a6 gene of the nakedcarp (Gymnocypris przewalskii) was expressed in various tissues, such as gills, liver, kidneys and intestines, and that the upregulation of SLC26A6 increased HCO3 − secretion and the Cl − absorption in the cells (Ping et al, 2015). Notably, several studies have shown that elevated chloride concentrations in the aquatic environment reduce the toxic effects of nitrite on aquatic animals, because both nitrite ions and chloride ions compete for the same site of active transport (Alcaraz and Espina, 1994;Jiann-Chu and Lee, 1997;Sha-Yen and Chen, 1998;Yildiz and Benli, 2004;Kozák et al, 2005;Camargo and Alonso, 2006;Alonso and Camargo, 2008;Zhang et al, 2015). Therefore, we hypothesized that the upregulation of SLC26A6 in nitrite-tolerant shrimp increases the absorption of chloride ions, forcing chloride ions and nitrite ions compete for the same site of active transport on the plasma membrane and various organelle membranes, resulting in enhanced nitrite tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Sowers et al (2004) menambahkan bahwa nitrit pada krustase dapat menyebabkan hipoksia dan gangguan pernafasan. Nitrit juga dapat menyebabkan menurunnya kemampuan darah dalam membawa oksigen (Kozák et al 2005), merusak organ tubuh, dan menurunkan kekebalan tubuh (Camargo & Alonso 2006;Romano & Zeng 2009).…”
Section: Nitrit (No2)unclassified